Emotional intelligence and ICTs in School bullying - Tsompou, Eleni; Drakatos, Nikolaos; Karabatzaki, Zoi; Loukeris, Dionysis (Eximia, 2022)
This thesis explored how much students' emotional intelligence levels could predict their behavior as bullies or victims, as well as how much emotional intelligence could act as a protective or preventive factor against school bullying incidents, in order to identify the role of emotional intelligence in bullying incidents. The methodological strategy that was used was the literature review strategy. The analysis's findings demonstrated that emotional intelligence is associated with lower levels of engagement in bullying events because students who have greater levels of emotional intelligence are less likely to take part in bullying occurrences as bullies or victims. Additionally, bullied children have trouble understanding and controlling their emotions, but they have little trouble recognizing and expressing their emotions. It appears that neither bullies nor victims have the skills needed to control or regulate their emotions. As a result, the enhancement of intervention programs may be aided by the measurement of students' emotional intelligence levels, which also effects as a protective and preventative measure. Children are increasingly using mobile phones and computers in their daily lives since communication has become easier. Children also use the Internet and two-way communication media more frequently, in addition to transfer a lot of information. Researchers have looked into the characteristics of cyber-bully perpetrators and victims, as well as the incidence rate of cyber-bullying and victimization (Ybarra & Mitchell, 2004; Li, 2006; Juvonen & Gross, 2008). The problem of "cyber-bullying" has been getting worse in every country as Internet use has increased